Flexible and foldable composite films based on polyimide/phosphorene hybrid aerogel and phase change material for infrared stealth and thermal camouflage - Shi, Tao; Zheng, Zhiheng; Liu, Huan; Wu, Dezhen; Wang, Xiaodong (Composites science and technology, 2022)
Infrared stealth technology plays a vital role in development of defense industry and new military equipment. The current study focused on a novel type of flexible and foldable composite films based on polyimide (PI)/phosphorene (PR) hybrid aerogel and phase change material (PCM) for infrared stealth and thermal camouflage applications. The composite films were successfully obtained by fabricating a PI/PR hybrid aerogel through prepolymerizaton, film casting, freeze-drying, and thermal imidization, followed by vacuum impregnation of polyethylene glycol (PEG) as a PCM into the aerogel framework. The combination of PI and PR nanoflakes endows the hybrid aerogel with an effective enhancement in mechanical properties, near infrared absorption, and infrared photothermal conversion. The resultant composite films not only present prominent tensile and fatigue-resistant performance but also exhibit a good thermal regulation capability with a high latent-heat capacity of over 150 J/g. More importantly, the composite films demonstrate good infrared stealth and thermal camouflage performance on the high-temperature targets through effective thermal buffer and insulation. With ultralight, flexible, foldable, shape-tunable, and thermal self-regulatory characteristics, the PI/PR aerogel/PEG composite films developed by this work exhibit great application potential in infrared stealth and thermal camouflage for new military equipment. [Display omitted] •A flexible and foldable composite film was designed for infrared stealth and thermal camouflage.•The film was based on the polyimide/phosphorene hybrid aerogel and phase change material.•The introduction of phosphorene enhances infrared absorption and photothermal conservation.•The film exhibit a good thermal regulation ability to buffer thermal swings.•The film shows great potential for stealth and camouflage applications in new military equipment.